Letter from James Curtis Booth to A. L. Snowden, June 19, 1883 - Booth, James Curtis (1883)
James Curtis Booth (1810-1888) writes to Archibald Loudon Snowden (1835-1912), Superintendent of the United States Mint at Philadelphia from 1879 to 1885, with a pro forma report on the Mint's shortages for the fiscal year.
Keywords: Booth, James Curtis, 1810-1888; Snowden, Archibald Loudon, 1835-1912; United States Mint; Mint of the United States